Optimized design and experiments of a rotary-extensive-type flowerpot seedling transplanting mechanism - Yin, Daqing; Wang, Jiazhao; Zhang, Shuo; Zhang, Nuoyi; Zhou, Maile (International Journal of Agricultural and Biological Engineering, 2019)
To realize the mechanization of flowerpot seedling transplanting, a creative mechanism to transplant flowerpot seedlings was designed. The mechanism is based on noncircular gear in combination with a transplanting arm equipped with an extensive seedling pick-up device to transplant the flowerpot seedlings from the growing tray to the flowerpot, which in accordance with the transplanting agronomy requirements. The working principles of a theoretical model and kinematic characteristics of the transplanting mechanism were analyzed. The computer-aided analysis and optimization software based on Visual Basic 6.0 was developed and used to obtain a set of special trajectory and attitude parameters satisfying the transplanting operation requirements. The optimized parameters were used for virtual manufacturing and simulation testing of the transplanting mechanism. The virtual prototype testing results are consistent with the theoretical analysis, verifying the structural design validity and rationality. The high-speed photography was used in a bench test of the transplanting mechanism with “Salvia Splendens” pot seedlings as test samples. The trajectory and attitudes of the theoretical analysis, virtual test, and physical prototype test were essentially identical. The bench test results showed that the success rate was 91.67% for the seedling pick-up device penetrating into the root mass at 35 mm, thus, the quality of the extracting seedling was satisfactory. Keywords: transplanting mechanism, rotary-extensile type, pot seedlings, flowers DOI: 10.25165/j.ijabe.20191206.5188 Citation: Yin D Q, Wang J Z, Zhang S, Zhang N Y, Zhou M L. Optimization design and experiments of a rotary-extensile type flowerpot seedling transplanting mechanism. Int J Agric & Biol Eng, 2019; 12(6): 45–50.